Investigation of an Innovative Rotor Modification for a Small-Scale Horizontal Axis Wind Turbine - Artur Bugała; Olga Roszyk (Energies, 2020)
This paper presents the results of the computational fluid dynamics (CFD) simulation of the airflow for a 300 W horizontal axis wind turbine, using additional structural elements which modify the original shape of the rotor in the form of multi-shaped bowls which change the airflow distribution. A three-dimensional CAD model of the tested wind turbine was presented, with three variants subjected to simulation: a basic wind turbine without the element that modifies the airflow distribution, a turbine with a plano-convex bowl, and a turbine with a centrally convex bowl, with the hyperbolic disappearance of convexity as the radius of the rotor increases. The momentary value of wind speed, recorded at measuring points located in the plane of wind turbine blades, demonstrated an increase when compared to the base model by 35% for the wind turbine with the plano-convex bowl, for the wind speed of 5 m/s, and 31.3% and 49% for the higher approaching wind speed, for the plano-convex bowl and centrally convex bowl, respectively. The centrally convex bowl seems to be more appropriate for higher approaching wind speeds. An increase in wind turbine efficiency, described by the power coefficient, for solutions with aerodynamic bowls was observed.